Social Media and Large Carnivores: Sharing Biased News on Attacks on Humans - Nanni, Veronica; Caprio, Enrico; Bombieri, Giulia; Schiaparelli, Stefano; Chiorri, Carlo; Mammola, Stefano; Pedrini, Paolo; Penteriani, Vincenzo (Frontiers in Ecology and Evolution, 2020)
The Internet and social media (SM) have profoundly changed the way the public receives and transmits news. The ability of the web to quickly disperse information both geographically and temporally allows SM to reach a much wider audience compared to traditional mass media. A powerful role is played by sharing, as millions of people routinely share news on SM platforms, influencing each other by transmitting their mood and feelings to others through emotional contagion. Thus, SM has become crucial in driving public perception and opinion. Humans have an instinctive fear of large carnivores, but such a negative attitude may be amplified by news media presentations and their diffusion on SM. Here, we investigated how reports of predator attacks on humans published in online newspapers spread on SM. By means of multi-model inference, we explored the contribution of four factors in driving the number of total shares (NTS) of news reports on SM: the graphic/sensationalistic content, the presence of images, the species, as well as the newspaper coverage. According to our results, the information delivered by SM is highly biased toward a graphic/sensationalistic view of predators. Thus, such negative coverage might lead to an unjustified and amplified fear in the public with consequent lower tolerance towards predators and decrease in the support for conservation plans. However, because SM represents a powerful communication tool, its role might be reversed to positive if used appropriately. Thus, constant engagement of scientists on SM would be needed to both disseminate more accurate information on large carnivores and stem the tide of misinformation before its widespread diffusion, a crucial step for effective predator conservation.